2020
DOI: 10.1002/jib.623
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of protein-polyphenol interactions in beer during forced aging

Abstract: Proteins and proteinaceous material were extracted by acetone precipitation of beer that had undergone forced aging through 0 (control), 5 (medium) or 10 (high) heat/chill cycles (60°C 48h/0°C 24h). Size exclusion chromatography analysis of the crude beer extract showed that forced ageing led to a significant increase in binding of phenolic compounds to Protein Z and especially to lipid transfer protein 1 (LTP1). Protein‐polyphenol conjugates were also present in high molecular weight (> 100 kDa) and low molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The treatment condition and time were determined by the experimental purpose [ 4 , 9 ]. For example, Jongberg et al, used a forced aging method to investigate the haze formation in commercial beer [ 10 ]. The procedure is as follows: beer was exposed to aging treatment by heat/chill cycles of 60 °C for 48 h, followed by 0 °C for 24 h, according to the Analytica-EBC method 9.30 with slight modifications.…”
Section: The Methodologies For Measurements Of Haze In Beermentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment condition and time were determined by the experimental purpose [ 4 , 9 ]. For example, Jongberg et al, used a forced aging method to investigate the haze formation in commercial beer [ 10 ]. The procedure is as follows: beer was exposed to aging treatment by heat/chill cycles of 60 °C for 48 h, followed by 0 °C for 24 h, according to the Analytica-EBC method 9.30 with slight modifications.…”
Section: The Methodologies For Measurements Of Haze In Beermentioning
confidence: 99%
“…Forced aging of beer experiments have shown significant losses of gallic acid, salicylic acid, hydroxy-phenyl lactic acid, chlorogenic acid, epicatechin, vanillic acid, ferulic acid, pyrocatechuic acid, and luteolin during the forced aging. It was supposed that these phenolic compounds took part in the colloidal changes, proposedly upon polymerization into tannins [ 10 , 54 ]. It has been reported that proanthocyanidins, one of the flavanol compounds, were important for the haze stability of beer.…”
Section: The Reasons For Haze Formation In Beermentioning
confidence: 99%
“…Various kinds of proteins (e.g., whey protein, casein, and gelatin) and polyphenols (e.g., tannic acid, curcumin, and phenolic acids) have been shown to form protein-polyphenol complexes with different functional properties (15)(16)(17)(18). For example, chlorogenic acid was reported to bind to casein and WP through non-covalent interactions, which altered the structure, solubility, and foaming capacity of the proteins (19).…”
Section: Introductionmentioning
confidence: 99%
“…However, milk tea is a complex and dispersed system composed of many ingredients [ 3 ]. During its preparation, due to the interaction of tea polyphenols with proteins, compounds can easily flocculate and precipitate [ 4 ]. Even solid milk tea flocculates and forms polyphenol–protein complexes after long-term storage [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proteins and proteinaceous material were extracted through the acetone precipitation of beer that had undergone forced aging. Treatment of the crude beer extract with sulphite (2M) dissociated the protein–polyphenol bonds of lipid transfer protein 1 (LTP1) and Protein Z, which were generated during moderate forced aging [ 4 ].…”
Section: Introductionmentioning
confidence: 99%